Lifestyle habits and fatigue among people with systemic lupus erythematosus and matched population controls. (August 2015) - Pettersson, S; Boström, C; Eriksson, K; Svenungsson, E; Gunnarsson, I; Henriksson, E Welin
Objective: The objective of this paper is to identify clusters of fatigue in patients with systemic lupus erythematosus (SLE) and matched controls, and to analyze these clusters with respect to lifestyle habits, health-related quality of life (HRQoL), anxiety and depression. Methods: Patients with SLE ( n = 305) and age- and gender-matched population controls ( n = 311) were included. Three measurements of fatigue (Fatigue Severity Scale (FSS), Vitality (VT, from SF-36) and Multidimensional Assessment of Fatigue scale (MAF) and hierarchic cluster analysis were used to define clusters with different degrees of fatigue. Lifestyle habits were investigated through questionnaires. HRQoL was assessed with the SF-36 and anxiety/depression with the Hospital Anxiety and Depression Scale. Results: Three clusters, denominated "High, " "Intermediate" and "Low" fatigue clusters, were identified. The "High" contained 80% patients, and 20% controls (median; VT 25, FSS 5.8, MAF 37.4). These had the most symptoms of depression (51%) and anxiety (34%), lowest HRQoL ( p < 0.001) and they exercised least frequently. The "Intermediate" (48% patients and 52% controls) (median; VT 55, FSS 4.1, MAF 23.5) had similarities with the "Low" regarding sleep/rest whereas social status and smoking were closer to the "High." The"Low" contained 22% patients and 78% controls (median; VT 80, FSS 2.3, MAF 10.9). They had the highest perceived HRQoL ( p < 0.001), least symptoms of anxiety (10%), no depression, smoked least (13%) and reported the highest percentage (24%) of exercising ≥3 times/week. Conclusion: Fatigue is common, but not a general feature of SLE. It is associated with depression, anxiety, low HRQoL and less physical exercise. Patients with SLE and population controls with a healthy lifestyle reported lower levels of fatigue. Whether lifestyle changes can reduce fatigue, which is a major problem for a majority of SLE patients, needs to be further explored.